Policy options to strengthen the cassava and rice supply chains - Zhang, Xiaobo; Whitney, Edward (International Food Policy Research Institute, 2012)
Nigeria is the world’s largest cassava producer and Africa’s largest rice importer. The government and private sector should figure out ways to enhance cassava’s competitiveness in the international market and improve the efficiency of domestic rice production and processing. A range of policies and initiatives can strengthen cassava and rice supply chains, all the way from production to marketing. However, because of the country’s massive size and diversity, different regions may face different constraints; following a decentralized approach to designing industrial policies and initiatives is the best course of action for Nigeria.